2017
DOI: 10.5849/fs-2016-047
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Estimates of Small Diameter Planted and Natural-Origin Loblolly Pines Show Major Departures from the National Biomass Estimator Equations

Abstract: As southern pine forests (both planted and naturally regenerated) are more heavily used to provide biomass for the developing energy sectors and carbon sequestration, a better understanding of models used to characterize regional biomass estimates is needed. We harvested loblolly pines (Pinus taeda L.) between 0.5 and 15 cm dbh from several plantations and naturally regenerated stands in southeastern Arkansas to evaluate allometric relationships based on stand origin. In this process, each pine was separated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Compared to the PA models, the DV models successfully reduced the estimation bias by 35.80%, 41.65%, 12.57%, and 6.35%, and for the foliage, branch, stem, and root biomass, respectively (calculated using RMSE, Equation (7)). These findings are in line with previous research by Zeng [ 9 ], Schurel et al [ 31 ], and Widagdo et al [ 24 ], which confirmed the importance of considering the origin’s effect on biomass models of Chinese fir ( Cunninghamia lanceolata ), loblolly pine ( Pinus taeda ), and larch ( Larix gmelinii ) in southern China, Arkansas, and northeast China, respectively. Better performance of origin-based biomass models might also be related to a major shift in productivity allocation (i.e., stand density or site productivity) between the planted and natural forest, leading to differences in their tree features, such as wood density [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared to the PA models, the DV models successfully reduced the estimation bias by 35.80%, 41.65%, 12.57%, and 6.35%, and for the foliage, branch, stem, and root biomass, respectively (calculated using RMSE, Equation (7)). These findings are in line with previous research by Zeng [ 9 ], Schurel et al [ 31 ], and Widagdo et al [ 24 ], which confirmed the importance of considering the origin’s effect on biomass models of Chinese fir ( Cunninghamia lanceolata ), loblolly pine ( Pinus taeda ), and larch ( Larix gmelinii ) in southern China, Arkansas, and northeast China, respectively. Better performance of origin-based biomass models might also be related to a major shift in productivity allocation (i.e., stand density or site productivity) between the planted and natural forest, leading to differences in their tree features, such as wood density [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…As one of the most superior predictors for predicting biomass, diameter at breast height (D) has been widely applied in a large number of tree-level species’ allometric equations across regions and forest types [ 7 , 31 ]. However, researchers still put a strong effort into increasing the biomass equation’s accuracy by adding more supporting independent predictors, such as tree total height (H), crown length, crown radius, wood density, and tree/stand age [ 6 , 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, available woody biomass and the carbon stored at early stages are often neglected. Only a few studies address the estimation of small diameter tree biomass in tropical dry forests [14,17], in temperate deciduous forest [15,18], and in temperate pine forest [19]. Ideally, the biomass equations should be developed covering all size classes without discontinuity at any tree size.…”
Section: Introductionmentioning
confidence: 99%